The Influence of Digital Marketing, Service Quality, and Product Innovation on Customer Loyalty in Beauty Industry - Ancello G. O. Kalaij; Yunus Handoko; Ike Kusdyah Rachmawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The beauty industry in Indonesia is experiencing rapid development, driven by ever-changing beauty trends and increasing digital penetration. This study aims to analyze the influence of digital marketing strategies, service quality, and product innovation on customer loyalty at Beauty Eyebrow Lash and Nail Jakarta. Data were collected through a survey of 99 active customer respondents using a questionnaire based on a Likert scale of 1-5. Data analysis techniques included multiple linear regression, normality test (Kolmogorov-Smirnov), multicollinearity test (VIF), heteroscedasticity test (Glejser), F-test for simultaneous effects, and t-test for partial effects on customer loyalty. The results of the analysis show that the three independent variables have a positive and significant effect on customer loyalty, both partially and simultaneously. Digital marketing strategies, such as collaboration with influencers, superior service quality, and relevant product innovation, have been shown to increase customer engagement and commitment. This study concludes that these factors significantly contribute to strengthening customer loyalty at Beauty Eyebrow Lash and Nail Jakarta, supporting the business’s success in facing increasingly tight competition in the beauty industry.